TVRI mediamorphosis: Transformation from news TV broadcasting to commercial broadcasting through the TVRI Klik Channel - Sudarsono, Achmad Budiman; Olivia, Helen (Universitas Bunda Mulia, 2026)
This research aims to understand the mediamorphosis process in TVRI's transformation from conventional to digital media, with a case study on TVRI Klik broadcast and a focus on TVRI World channel. Data was analysed qualitatively through netnography methods, exploring the dynamics of digital platforms, user preferences, content consumption patterns, and reactions to media changes. The results show that the transformation of TVRI Klik, which began in 2017-2018, marks a significant shift towards more interactive and integrated broadcasting. TVRI World aims to combine international broadcasts with local content. Despite facing technical challenges, co-operation with social media platforms and streaming technologies helped increase visibility and audience engagement. This transformation shows how TVRI can adapt to the digital age, provide more diverse and flexible content, and strengthen its role as an educative and informative public television.